Pengaruh Game Mobile Legends terhadap Minat Belajar Mahasiswa/i Fakultas Sains dan Teknologi UIN Alauddin Makassar - Nawawi, M. Ichsan; Pathuddin, Hikmawati; Syukri, Nabila; Alfidayanti, Alfidayanti; Poppysari, Sartika; Saputri, Saputri; Ramdani, Muhammad; Jun, Muhammad; Marsuki, Ismail (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2021)
This study aims to determine the effect of mobile legends online games on the interest in learning of students of the Faculty of Science and Technology UIN Alauddin Makassar. The research method used in this study is using a correlational quantitative approach, where the population taken is active students who play Mobile Legend online games at FST UINAM. To determine the sample used quota sampling technique by determining the portion of 10 people in each department in the Faculty of Science and Technology. Retrieval of respondent data through google form then the data is processed with the SPSS application. Mobile legend online game is one of the top 5 most played MOBA games on the android market and much favored by students, none other than students. The Mobile Legend online game variable consists of three indicators, 1) Media Exposure, 2) Play Motivation and 3) Imitation Behavior. From the results of the analysis carried out by using a hypothesis test with a calculated F value of 3.620 > F table 2.71, it can be concluded that there is an effect of Media Exposure (X1), Play Motivation (X2) and Imitation Behavior (X3) simultaneously on Learning Interest (Y). The value of R2 (R Square) 0.112 means that the influence of the Mobile Legend Online Game variable on learning interest is 11.2% while the effect is influenced by other factors not examined in this study.